Measurement Invariance of Science Self-Efficacy Scale in PISA - Nermin Kıbrıslıoğlu Uysal; Çiğdem Akın Arıkan (International Journal of Assessment Tools in Education)
The aim of this study is to find out whether the science self-efficacy scale in PISA 2006 and PISA 2015 applications ensure measurement invariance. Sample of the study consists of 4791 students in PISA 2006 and 5071 students in PISA 2015 implementation. Multi-group Confirmatory Factor Analysis (MGCFI) was performed to determine invariance of the science self-efficacy scale across year and gender. The analyses were concudted in SPSS and Lisrel programs. Invariance stages were examined (ΔCF and ΔTL) by means of the comparıson of fit indexes. The results of the study indicated that the science self-efficacy scale satisfied all stages of invariance by gender both in 2006 and 2015. Also only structural and metric invariance was provided for both genders across years. Configural invariance, metric invariance and scalar invariance were satisfied for the total group across years.